Positive temperature coefficient melting barrier material, diaphragm for lithium ion battery and lithium ion battery

By applying a positive temperature coefficient melt barrier material on the lithium-ion battery separator, it uses its high thermal conductivity and rapid phase change characteristics to solve the thermal runaway and fire explosion problems of lithium-ion batteries under needle puncture conditions, and improve the battery Safe and maintain electrical performance.

CN119432327APending Publication Date: 2025-02-14STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3

Patent Information

Application Number
CN202411077587.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The problem of lithium-ion batteries causing thermal runaway and fire explosions under needle puncture conditions is difficult for the prior art to effectively solve this problem without affecting the performance of the battery.

Method used

Using a positive temperature coefficient melting barrier material, this material is matched with a molten agent microsphere and a positive temperature coefficient composite microsphere. It has high thermal conductivity and rapid phase change characteristics, and can quickly melt when the ambient temperature reaches a specific point and block the diaphragm. Ion transfer channel, isolate the battery reaction.

Benefits of technology

It effectively solves the thermal runaway and fire explosion problems of lithium-ion batteries under needle puncture conditions, improves the safety of the battery, and does not affect the electrical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432327A_ABST
    Figure CN119432327A_ABST
Patent Text Reader

Abstract

The invention relates to a positive temperature coefficient melting barrier material, a diaphragm for a lithium ion battery and the lithium ion battery. The positive temperature coefficient melting barrier material comprises melting agent microspheres and positive temperature coefficient composite material microspheres, the melting agent microspheres comprise a first high-molecular polymer material; the positive temperature coefficient composite material microspheres comprise a second high-molecular polymer material and a conductive agent; the conductive agent includes a carbon-based conductive powder. According to the positive temperature coefficient melting barrier material, the melting agent microspheres and the positive temperature coefficient composite material microspheres are matched, and the obtained material has the characteristics of high heat conductivity, high phase change rate, self heat production and short-circuit current limitation, and can realize rapid cutting of an electronic loop, acceleration of melting hole blocking of a melting agent and cutting of an ion transmission channel; and the safety of the lithium ion battery under the needling working condition is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a positive temperature coefficient melting barrier material, a separator for a lithium-ion battery, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries have many advantages such as long cycle life, high energy efficiency, high safety and low cost, and are one of the most competitive products in the electrochemical energy storage power station. However, one of the biggest pain points of lithium iron phosphate energy storage batteries is that under the condition of needle puncture, the rapid heat generation and melting of the diaphragm under the condition of large flow rate causes large-area short circuit of the positive and negative pole pieces, which in turn causes thermal runaway of the battery, fire and explosion.

[0003] CN115020909A discloses a lithium ion battery diaphragm and a preparation method thereof, comprising: (1) mixing a polyolefin resin, an antioxidant, and a porogen and heating them to a molten state, extruding them through a die and then cooling them to form a cast sheet; (2) sequentially performing a first longitudinal stretching and a first transverse stretching on the cast sheet to obtain a stretched film; (3) performing a second longitudinal stretching on the stretched film; (4) then performing a second transverse stretching; (5) extracting the porogen in the diaphragm to obtain an extracted diaphragm; (6) performing a third longitudinal stretching on the extracted diaphragm; (7) then performing a third transverse stretching; (8) then sequentially performing a fourth transverse stretching and heat setting to obtain the lithium ion battery diaphragm. Although the disclosure improves the needle puncture strength to a certain extent by optimizing the preparation method of the diaphragm, it still cannot solve the problem of thermal runaway, fire and explosion of the battery caused by the melting of the diaphragm, and there is still a large safety hazard.

[0004] CN106848400A discloses an electrolyte for a high-safety lithium-ion battery and a lithium-ion battery thereof, specifically discloses an electrolyte for a high-safety lithium-ion battery, wherein a heat-blocking additive is added to the electrolyte, thereby improving the safety performance of the electrolyte, so that the assembled lithium-ion battery can stop the heat-generating reaction at high temperatures, thereby improving the safety of the lithium-ion battery. However, due to the introduction of the heat-blocking additive, the impedance of the battery increases, greatly affecting the electrical performance of the battery.

[0005] In summary, it is of great significance to solve the problem of battery thermal runaway, fire and explosion caused by puncture conditions without affecting battery performance. Summary of the invention

[0006] In order to solve the above technical problems, the present disclosure provides a positive temperature coefficient melt barrier material, a lithium ion battery diaphragm and a lithium ion battery. The positive temperature coefficient melt barrier material combines flux microspheres with positive temperature coefficient composite material microspheres, so that it has the characteristics of high thermal conductivity, fast phase change rate, self-heat generation, and short-circuit current limitation. The operating temperature range is 0-150°C, which plays an important role in the application of lithium ion batteries with traditional structures and improves the safety of lithium ion batteries under acupuncture conditions.

[0007] In a first aspect, the present disclosure provides a positive temperature coefficient melt barrier material, the positive temperature coefficient melt barrier material comprising flux microspheres and positive temperature coefficient composite material microspheres;

[0008] The flux microspheres include a first high molecular polymer material;

[0009] The positive temperature coefficient composite material microspheres include a second high molecular polymer material and a conductive agent; the conductive agent includes carbon-based conductive powder.

[0010] In addition, the present disclosure also provides a method for preparing a positive temperature coefficient molten barrier material, comprising:

[0011] (1) mixing the melted second polymer material and the conductive agent, and preparing positive temperature coefficient composite microspheres after ball milling;

[0012] (2) Mixing the positive temperature coefficient composite material microspheres obtained in step (1) with the flux microspheres to obtain a positive temperature coefficient molten barrier material.

[0013] The positive temperature coefficient molten barrier material obtained by the present invention has the following advantages: First, it will not undergo physical and chemical reactions with most solvents and electrolytes; Second, compared with traditional lithium ion diaphragms, the diaphragms coated with the positive temperature coefficient molten barrier material have higher thermal conductivity. When the ambient temperature reaches the Curie point of the positive temperature coefficient composite material and the phase change temperature of the flux, the positive temperature coefficient composite material can quickly increase the resistance, cut off the ion circuit, and transfer heat to the flux at the same time. The flux quickly melts, blocks the ion transmission channel of the diaphragm, isolates the battery reaction, and fundamentally solves the battery safety problem.

[0014] The method for preparing the positive temperature coefficient molten barrier material provided by the present disclosure has a simple process flow and is suitable for industrial production.

[0015] It should be noted that to obtain the positive temperature coefficient melting barrier material, the second high molecular polymer material must be compounded with the conductive agent to obtain a positive temperature coefficient composite material, and then mixed with the melting agent (first high molecular polymer material). If the three are mixed directly, it is equivalent to mixing excess melting agent with the conductive agent. On the one hand, the conductive agent content is too low, which will lead to weak thermal conductivity and fail to effectively improve the thermal response speed. On the other hand, because the proportion of the conductive agent is too low, the positive temperature effect of the positive temperature coefficient material becomes weak.

[0016] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.

[0017] As a preferred technical solution of the present disclosure, the first high molecular polymer material includes any one of polyethylene, chlorinated polyethylene, oxidized polyethylene, thermoplastic polyurethane rubber, polyamide, polyimide, polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, and polymethyl methacrylate, or a combination of at least two of them, such as a combination of polyethylene and ethylene-acrylic acid copolymer, a combination of polypropylene and oxidized polyethylene, a combination of polyamide, polyimide and polymethyl methacrylate, etc.

[0018] The first high molecular polymer material disclosed in the present invention is not limited to the above materials, and other conventional high molecular polymer materials in the art are also applicable.

[0019] As a preferred technical solution of the present disclosure, the second high polymer material includes any one of polyethylene, chlorinated polyethylene, oxidized polyethylene, thermoplastic polyurethane rubber, polyamide, polyimide, polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, and polymethyl methacrylate, or a combination of at least two of them, such as a combination of ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer and ethylene-acrylate copolymer, a combination of polyethylene and chlorinated polyethylene, etc.

[0020] The second high molecular polymer material disclosed in the present invention is not limited to the above materials, and other conventional high molecular polymer materials in the art are also applicable.

[0021] As a preferred technical solution of the present disclosure, the carbon-based conductive powder includes but is not limited to one or a combination of at least two of carbon powder, graphite, acetylene black, carbon nanotubes or graphene, such as a combination of carbon powder and graphite, a combination of carbon powder and acetylene black, a combination of acetylene black and graphene, etc.

[0022] In the present disclosure, the first polymer material, the second polymer material and the conductive agent material can be selected and used in combination according to the required Curie point of the positive temperature coefficient composite material and the phase transition temperature of the flux microspheres.

[0023] As a preferred technical solution of the present invention, the mass ratio of the flux microspheres to the positive temperature coefficient composite microspheres is (1-1200):(1-1000), for example, 1:3, 1:10, 1:100, 1:200, 1:500, 1:1000, 50:1, 500:1, 700:1, 1000:1 or 1200:1, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable, preferably (300-800):(200-900).

[0024] As a preferred technical solution of the present invention, the mass ratio of the second high molecular polymer material to the conductive agent is (15-30):1, for example, 15:1, 17:100, 19:1, 20:1, 22:1, 24:1, 26:1, 28:1 or 30:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0025] As a preferred technical solution of the present invention, the average particle size of the positive temperature coefficient melting barrier material is 0.1-10μm, for example, 0.1μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 8μm or 10μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable, preferably 5-10μm.

[0026] In a second aspect, the present disclosure further provides a lithium-ion battery separator, comprising a base layer and a coating layer disposed on at least one side of the base layer; the material of the coating layer comprises the positive temperature coefficient melting barrier material described in the first aspect.

[0027] Wherein, the base layer is a conventional lithium-ion battery separator in the prior art, including but not limited to a PP separator or a PE separator.

[0028] As a preferred technical solution of the present disclosure, the material of the coating layer also includes an additive.

[0029] Preferably, the auxiliary agent comprises a binder, and the binder includes but is not limited to styrene-butadiene rubber and / or sodium carboxymethyl cellulose.

[0030] The present disclosure also provides a method for preparing a lithium ion battery separator, comprising:

[0031] (1) mixing the positive temperature coefficient molten barrier material described in the first aspect with a solvent to obtain a mixed slurry;

[0032] (2) The slurry of step (1) is applied to at least one side of the surface of the base layer to obtain a separator for a lithium-ion battery.

[0033] Wherein, the solvent comprises water;

[0034] Preferably, the raw materials required for step (1) further include auxiliary agents, wherein the auxiliary agents include a binder, and the binder includes but is not limited to styrene-butadiene rubber and / or sodium carboxymethyl cellulose;

[0035] Preferably, the mass portion of the positive temperature coefficient melting barrier material is 1-100 parts, and the mass portion of the auxiliary agent is 0-30 parts;

[0036] Preferably, the mixing comprises ultrasonic treatment and mechanical stirring;

[0037] Preferably, the coating method includes spray coating, extrusion coating or transfer coating.

[0038] Preferably, as a preferred technical solution of the present disclosure, the thickness of the coating layer is 1-20 μm, for example, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm or 20 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0039] As a preferred technical solution of the present disclosure, the loading amount of the positive temperature coefficient melting barrier material relative to the base layer is 3-10 mg / cm 2 , for example 3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 7mg / cm 2 , 9mg / cm 2 or 10mg / cm 2 The above values ​​are not limited to the above values, and other values ​​not listed in the above values ​​are also applicable.

[0040] In a third aspect, the present disclosure further provides a lithium ion battery, wherein the lithium ion battery comprises the lithium ion battery separator according to the second aspect.

[0041] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:

[0042] (1) The positive temperature coefficient molten barrier material disclosed in the present invention will not dissolve or swell with most solvents and electrolytes, and when the ambient temperature reaches the Curie point of the positive temperature coefficient composite material and the phase transition temperature of the flux, the positive temperature coefficient composite material can quickly increase the resistance, cut off the electronic circuit, and transfer heat to the flux at the same time. The flux quickly melts, blocks the ion transmission channel of the diaphragm, isolates the battery reaction, and fundamentally solves the safety problem of the battery;

[0043] (2) The positive temperature coefficient melt barrier material disclosed in the present invention is simple and efficient to prepare and can be easily coated on a lithium-ion battery separator; and the obtained separator has good compatibility with the existing lithium-ion battery manufacturing system and can be directly introduced into the production system, with low processing cost and high economic benefit;

[0044] (3) The positive temperature coefficient molten barrier material disclosed in the present invention can form a microporous structure on the surface of the diaphragm, has little effect on the electrical properties of the lithium-ion battery, and has good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.

[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0047] Figure 1 It is a schematic diagram of the operation of the positive temperature coefficient melting barrier material under the needling condition shown in the embodiment of the present disclosure;

[0048] Among them, 1. positive electrode; 2. negative electrode; 3. separator; 31. base layer; 32. positive temperature coefficient composite material microspheres; 33. flux microspheres; 4. steel needles. DETAILED DESCRIPTION

[0049] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0050] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0051] Example 1

[0052] S1: mixing molten polyethylene and carbon powder, and obtaining polyethylene composite microspheres with a carbon powder content of 5 wt% by ball milling;

[0053] S2: 3000 g of polyethylene composite microspheres with a carbon powder content of 5 wt% and 1000 g of polyethylene microspheres were mixed, and fully ultrasonically dispersed in an aqueous solution to obtain positive temperature coefficient melt barrier material microspheres with an average particle size of 8 μm.

[0054] S3: Add 1000g of the above-prepared positive temperature coefficient melt barrier material microspheres, 20g of styrene-butadiene rubber and 10g of sodium carboxymethyl cellulose into 1200g of water, mix evenly to obtain a mixed slurry, and coat the mixed slurry on the surface of one side of the base layer by micro-gravure. After drying, a lithium-ion battery separator with a coating layer thickness of 20μm and a total thickness of 25μm is obtained.

[0055] The loading amount of the positive temperature coefficient melting barrier material relative to the base layer is 3 mg / cm 2 The base layer is a PP diaphragm with a porosity of 40%.

[0056] S4: The lithium-ion battery separator is wound with the positive electrode and the negative electrode to prepare a lithium-ion battery cell, and a thermal-sensitive safe lithium-ion battery is obtained after baking, liquid injection, formation and packaging;

[0057] Among them, the preparation of the positive electrode includes: mixing 90wt% of lithium iron phosphate, 5wt% of polyvinylidene fluoride (PVDF) and 5wt% of acetylene black with N-methylpyrrolidone (NMP) in mass percentage to obtain a positive electrode slurry; coating the obtained negative electrode slurry on an aluminum foil current collector, and obtaining a positive electrode sheet after drying and compacting.

[0058] The preparation of the negative electrode includes: mixing 85wt% of artificial graphite, 10wt% of sodium carboxymethyl cellulose (CMC) and 5wt% of conductive graphite with water in mass percentage to obtain a negative electrode slurry; coating the obtained negative electrode slurry on a copper foil current collector, and obtaining a negative electrode sheet after drying and compacting.

[0059] The electrolyte includes 12 wt % of lithium hexafluorophosphate (LiPF6), 85 wt % of dimethyl carbonate (DMC) and 3 wt % of vinylene carbonate (VC).

[0060] The coating layer faces the positive electrode side.

[0061] Example 2

[0062] S1: mixing molten ethylene-vinyl acetate copolymer and carbon powder, and obtaining ethylene-vinyl acetate copolymer composite microspheres having a carbon powder content of 6.25 wt % by ball milling;

[0063] S2: After stirring and evenly mixing 3000g of ethylene-vinyl acetate copolymer composite microspheres with a carbon powder content of 6.25wt% and 1000g of ethylene-vinyl acetate copolymer microspheres, a uniformly mixed positive temperature coefficient melt barrier material microspheres are obtained by ball milling. The average particle size of the prepared positive temperature coefficient melt barrier material microspheres is 10μm.

[0064] S3: Add 1000g of the above-prepared positive temperature coefficient melt barrier material microspheres, 30g of styrene-butadiene rubber and 10g of sodium carboxymethyl cellulose into 1200g of water, mix evenly to obtain a mixed slurry, and coat the mixed slurry on one side of the base layer by micro-gravure. After drying, a lithium-ion battery separator with a coating layer thickness of 20μm and a total thickness of 25μm is obtained.

[0065] The loading amount of the positive temperature coefficient melting barrier material relative to the base layer is 5 mg / cm 2 The base layer is a PP diaphragm with a porosity of 40%.

[0066] S4: Prepare the above-mentioned lithium ion battery separator by referring to the method in Example 1 to obtain a thermosensitive safe lithium ion battery.

[0067] Example 3

[0068] S1: mixing molten polypropylene and carbon powder, and obtaining polypropylene composite microspheres with a carbon powder content of 3 wt% by ball milling;

[0069] S2: After 3000g of polypropylene composite microspheres with a carbon powder content of 3wt% and 1000g of polypropylene microspheres are stirred and evenly mixed, a ball milling method is used to obtain evenly mixed positive temperature coefficient melt barrier material microspheres. The average particle size of the prepared positive temperature coefficient melt barrier material microspheres is 5μm.

[0070] S3: Add 1000g of the above-prepared positive temperature coefficient melt barrier material microspheres, 30g of styrene-butadiene rubber and 10g of sodium carboxymethyl cellulose into 1200g of water, mix evenly to obtain a mixed slurry, and coat the mixed slurry on one side of the base layer by micro-gravure. After drying, a lithium-ion battery separator with a coating layer thickness of 20μm and a total thickness of 25μm is obtained.

[0071] The loading amount of the positive temperature coefficient melting barrier material relative to the base layer is 10 mg / cm 2 The base layer is a PP diaphragm with a porosity of 40%.

[0072] S4: Prepare the above-mentioned lithium ion battery separator by referring to the method in Example 1 to obtain a thermosensitive safe lithium ion battery.

[0073] Example 4

[0074] S1: mixing molten polypropylene and carbon powder, and obtaining polypropylene composite microspheres with a carbon powder content of 5 wt% by ball milling;

[0075] S2: After 3000g of polypropylene composite microspheres with a carbon powder content of 5wt% and 1000g of polypropylene microspheres are stirred and evenly mixed, a ball milling method is used to obtain evenly mixed positive temperature coefficient molten barrier material microspheres. The average particle size of the prepared positive temperature coefficient molten barrier material microspheres is 10μm.

[0076] S3: Add 1000g of the above-prepared positive temperature coefficient melt barrier material microspheres, 30g of styrene-butadiene rubber and 10g of sodium carboxymethyl cellulose into 1200g of water, mix evenly to obtain a mixed slurry, and coat the mixed slurry on one side of the base layer by micro-gravure. After drying, a lithium-ion battery separator with a coating layer thickness of 20μm and a total thickness of 25μm is obtained.

[0077] The loading amount of the positive temperature coefficient melting barrier material relative to the base layer is 7 mg / cm 2 The base layer is a PP diaphragm with a porosity of 40%.

[0078] S4: Prepare the above-mentioned lithium ion battery separator by referring to the method in Example 1 to obtain a thermosensitive safe lithium ion battery.

[0079] Example 5

[0080] This embodiment refers to the method of Embodiment 2, except that in step S2, 3000 g of ethylene-vinyl acetate copolymer composite microspheres having a carbon powder content of 6.25 wt% are replaced with 3000 g of ethylene-vinyl acetate copolymer composite microspheres having a carbon powder content of 10 wt%.

[0081] Example 6

[0082] This embodiment refers to the method of Embodiment 3, except that in step S2, 3000 g of polypropylene composite microspheres having a carbon powder content of 3 wt% are replaced with 3000 g of polypropylene composite microspheres having a carbon powder content of 1 wt%.

[0083] Comparative Example 1

[0084] This comparative example refers to the method of Example 1, with the only difference being that step S1 is not performed. Therefore, in order to ensure that the total mass of the added materials in step S2 remains unchanged, 3000 g of polyethylene composite microspheres with a carbon powder content of 5 wt% and 1000 g of polyethylene microspheres are replaced with 4000 g of polyethylene microspheres.

[0085] Comparative Example 2

[0086] This comparative example refers to the method of Example 1, with the only difference being that in step S2, no flux microspheres are added, and to ensure that the total mass of material added in step S2 remains unchanged, 3000 g of polyethylene composite microspheres with a carbon powder content of 5 wt% and 1000 g of polyethylene microspheres are used to replace 4000 g of polyethylene composite microspheres with a carbon powder content of 5 wt%.

[0087] Comparative Example 3

[0088] This comparative example refers to the method of Example 1, except that the first high molecular polymer material, the second high molecular polymer material and the conductive agent are directly mixed instead of mixing in steps.

[0089] That is, step S1 and step S2 are not performed, but the molten polyethylene and carbon powder are mixed, and after ball milling, polyethylene composite microspheres with a carbon powder content of 3.75wt% and an average particle size of 8μm are obtained; in step S3, the polyethylene composite microspheres with a carbon powder content of 3.75wt% obtained above are used to replace the positive temperature coefficient molten barrier material microspheres.

[0090] Comparative Example 4

[0091] This comparative example provides a lithium ion battery separator, wherein the lithium ion battery separator is a PP separator with a porosity of 40%.

[0092] The above-mentioned lithium ion battery separator was prepared by referring to the method in Example 1 to obtain a thermosensitive safe lithium ion battery.

[0093] (i) At room temperature (25±1°C), the thermal conductivity of the positive temperature coefficient molten barrier material microspheres obtained in Examples 1-6 and the material microspheres obtained in Comparative Examples 1-3 were measured using a laser flash meter. The results are shown in Table 1.

[0094] Table 1

[0095]

[0096]

[0097] As shown in Table 1, the positive temperature coefficient molten barrier material has a high thermal conductivity, reaching 0.26 W·m -1 ·K -1As above. Compared with Example 1, Comparative Example 1 has a lower thermal conductivity due to the lack of the positive temperature coefficient composite material. Compared with Example 1, Comparative Example 2 uses only the positive temperature coefficient composite material as a coating layer without adding a flux. Although it has a higher thermal conductivity, it is difficult to achieve the effect of melting and plugging the holes within seconds under short-circuit conditions without the use of a flux. In Comparative Example 3, no step-by-step mixing was performed, but the three materials were mixed in one step, resulting in too little conductive agent in the positive temperature coefficient composite material, reduced thermal conductivity, and a lack of independent flux particles, which made it impossible to increase the melting and plugging speed.

[0098] (ii) An electrochemical workstation was used to perform internal resistance tests on the lithium-ion batteries obtained in Examples 1-6 and Comparative Examples 1-4 at different temperatures. The results are shown in Table 2.

[0099] Table 2

[0100] 25℃ 120℃ for 10min 120℃ for 30min Example 1 0.525mΩ 6.224mΩ 9.322mΩ Example 2 0.535mΩ 7.241mΩ 10.232mΩ Example 3 0.530mΩ 6.940mΩ 9.254mΩ Example 4 0.527mΩ 7.038mΩ 10.154mΩ Example 5 0.518mΩ 2.349mΩ 8.102mΩ Example 6 0.543mΩ 4.671mΩ 6.846mΩ Comparative Example 1 0.545mΩ 1.324mΩ 7.342mΩ Comparative Example 2 0.531mΩ 5.764mΩ 8.954mΩ Comparative Example 3 0.524mΩ 3.564mΩ 8.467mΩ Comparative Example 4 0.531mΩ 1.034mΩ 6.746mΩ

[0101] As can be seen from Table 2, the thermal sensitivity range of the positive temperature coefficient melting barrier material obtained in the example is 100-120°C, and the lithium-ion battery prepared using the positive temperature coefficient melting barrier material disclosed in the present invention has strong thermal responsiveness. Examples 1-4 can show thermal responsiveness within 10 minutes, and the resistance is significantly improved, which can more quickly suppress the occurrence of battery thermal runaway.

[0102] In Example 5, too much conductive agent is added, resulting in too little addition of the second high molecular polymer material in the positive temperature coefficient composite material. When the ambient temperature reaches the Curie point, the electronic circuit cannot be cut off by quickly increasing the resistance. In Example 6, too little conductive agent is added in the positive temperature coefficient composite material, and the thermal responsiveness becomes weak, and the electronic circuit cannot be quickly cut off.

[0103] In Comparative Example 1, no positive temperature coefficient composite material was added, resulting in a slow response time and increased danger. Although the response time of Comparative Example 2 was faster, there was no synergistic effect of the flux, and the ion circuit could not be cut off within seconds, and fire and explosion still occurred under the needle puncture condition. In Comparative Example 3, the three materials were mixed in one step, resulting in a smaller amount of conductive agent added, a lower thermal conductivity, a slower thermal response, and a worse battery safety.

[0104] (III) The 280Ah lithium-ion batteries prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to high-temperature charge and discharge tests. The test process was to subject the fully charged cells obtained after the lithium-ion batteries were charged and discharged to a charge and discharge experiment in an environment of 25°C. The results are shown in Table 3.

[0105] Table 3

[0106] Charging capacity(Ah) Discharge capacity(Ah) Example 1 283.0 281.4 Example 2 281.8 280.6 Example 3 282.1 281.3 Example 4 281.0 280.9 Example 5 280.6 279.4 Example 6 282.3 281.1 Comparative Example 1 282.2 280.8 Comparative Example 2 282.5 280.9 Comparative Example 3 278.6 276.0 Comparative Example 4 280.1 278.7

[0107] From the data in Table 3, the following conclusions can be drawn: there is no significant difference in the charge and discharge capacity of the batteries of Examples 1-6 and Comparative Examples 1-4, and the use of a positive temperature coefficient molten barrier material coated on the diaphragm does not have a significant effect on the battery capacity.

[0108] (IV) The lithium-ion batteries prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to needle puncture tests to test the difference in surface temperature of the 100% SOC lithium-ion batteries after being punctured by an 8mm steel needle at a speed of 25mm / s, and the fire and explosion phenomena of the batteries in the test were analyzed. The results are shown in Table 4. When the lithium-ion batteries obtained in the examples were subjected to needle puncture tests, the working schematic diagram of the positive temperature coefficient melt barrier material is shown in Figure 1 shown.

[0109] Figure 1 In the figure, a positive electrode 1, a separator 3 and a negative electrode 2 are stacked in sequence from top to bottom; wherein the separator 3 includes a base layer 31 and a coating layer coated on one side of the base layer 31, the coating layer faces the side of the positive electrode 1; the material of the coating layer includes positive temperature coefficient composite microspheres 32 and flux microspheres 33. An 8mm steel needle 4 is inserted perpendicularly to the positive electrode 1 at a speed of 25mm / s, causing an internal short circuit in the battery, and the positive temperature coefficient composite microspheres 32 and flux microspheres 33 work together, the flux microspheres 33 melt, and the pores of the base layer 31 are blocked to ensure the safety of the battery.

[0110] Table 4

[0111] Puncture test results Example 1 pass Example 2 pass Example 3 pass Example 4 pass Example 5 pass Example 6 pass Comparative Example 1 Thermal runaway fire Comparative Example 2 Thermal runaway fire Comparative Example 3 Thermal runaway fire Comparative Example 4 Thermal runaway fire

[0112] It can be seen from Table 4 that the lithium-ion batteries made of the positive temperature coefficient melting barrier material disclosed in Examples 1-6 all passed the needle puncture test, which effectively improved the safety performance of the lithium-ion batteries and is of great significance to the development of lithium-ion batteries.

[0113] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0114] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A positive temperature coefficient melting barrier material, characterized in that: The positive temperature coefficient melting barrier material comprises melting agent microspheres and positive temperature coefficient composite material microspheres; The flux microspheres include a first high molecular polymer material; The positive temperature coefficient composite material microspheres include a second high molecular polymer material and a conductive agent; the conductive agent includes carbon-based conductive powder.

2. The positive temperature coefficient melting barrier material according to claim 1, characterized in that: The first high molecular polymer material includes any one of polyethylene, chlorinated polyethylene, oxidized polyethylene, thermoplastic polyurethane rubber, polyamide, polyimide, polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, and polymethyl methacrylate, or a combination of at least two thereof.

3. The positive temperature coefficient melting barrier material according to claim 1 or 2, characterized in that: The second high molecular polymer material includes any one of polyethylene, chlorinated polyethylene, oxidized polyethylene, thermoplastic polyurethane rubber, polyamide, polyimide, polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, and polymethyl methacrylate, or a combination of at least two thereof.

4. The positive temperature coefficient melting barrier material according to any one of claims 1 to 3, characterized in that: The mass ratio of the flux microspheres to the positive temperature coefficient composite material microspheres is (1-1200):(1-1000), preferably (300-800):(200-900).

5. The positive temperature coefficient melting barrier material according to any one of claims 1 to 4, characterized in that: The mass ratio of the second high molecular polymer material to the conductive agent is (15-30):

1.

6. The positive temperature coefficient melting barrier material according to any one of claims 1 to 5, characterized in that: The average particle size of the positive temperature coefficient melting barrier material is 0.1-10 μm, preferably 5-10 μm.

7. A separator for a lithium ion battery, characterized in that: The lithium-ion battery separator comprises a base layer and a coating layer disposed on at least one surface of the base layer; the material of the coating layer comprises the positive temperature coefficient melting barrier material described in any one of claims 1-6.

8. The lithium ion battery separator according to claim 7, characterized in that The thickness of the coating layer is 1-20 μm; Preferably, the loading amount of the positive temperature coefficient melting barrier material relative to the base layer is 3-10 mg / cm 2 .

9. The lithium ion battery separator according to claim 7 or 8, characterized in that: The material of the coating layer also includes an additive.

10. A lithium ion battery, characterized in that: The lithium ion battery comprises the lithium ion battery separator according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • High-safety electrolyte for lithium ion battery and lithium ion battery

    CN106848400A

Cited By

  • Safety coating for battery electrode plate and electrode plate

    CN121565793A